Designing reverse logistics network for a case study of home-care health medical device waste management: Implications for Industry 4.0 supply chains. Issue 10 (2022) - Sar, Kubra; Ghadimi, Pezhman
Abstract: This study presents a reverse logistics network design (RLND) model for medical product waste management generated as part of home health care operation. The aim of this paper is to develop a mathematical model that maximizes collected waste amount by utilizing real-time updating number of customers in the network and their changing demands. The efficiency and applicability of the developed model was validated by a randomly generated small dataset based on a case study in home care health management sector using Pyomo optimization solver package.